Changes of the radiation characteristics of surface of tungsten as a result of influence of helium ion beams - Manuilenko, O.V.; Prokhorenko, E.M.; Pavlii, K.V.; Zajtsev, B.V.; Dubniuk, S.N.; Lytvynenko, V.V.; Prokhorenko, T.G. (Вопросы атомной науки и техники, 2022)
The change in the radiation characteristics of the surface of tungsten was studied. Helium ions beams with energies of 0.12 and 4 MeV were used. Curves of ionization and damage are got on length of free run of ions of helium. The change the radiation characteristics of the surface of tungsten was studied. In the case of treatment with a beam of helium ions with energies of 0.12 MeV an increase in the hardness of the tungsten surface was found. Bubbles development has been studied. The appearance of tungsten tendrils around the bubbles, the formation of hills and valleys was considered. Досліджувалася зміна радіаційних характеристик поверхні вольфраму. Застосовувалися пучки іонів гелію з енергіями 0,12 і 4 MеВ. Отримані криві іонізації і пошкоджень по довжині вільного пробігу іонів гелію. Знайдено збільшення твердості поверхні вольфрамової мішені в разі обробки пучком іонів гелію з енергією 0,12 MеВ. Вивчався розвиток бульбашок. Розглядалися поява вольфрамових вусиків, утворення горбів і долин. Исследовалось изменение радиационных характеристик поверхности вольфрама. Применялись пучки ионов гелия с энергиями 0,12 и 4 MэВ. Получены кривые ионизации и повреждений по длине свободного пробега ионов гелия. Найдено увеличение твердости поверхности вольфрамовой мишени в случае обработки пучком ионов гелия с энергией 0,12 MэВ. Изучалось развитие пузырьков. Рассматривались появление вольфрамовых усиков, образование холмов и долин.